Modelling of fatigue crack growth following overloads - Voorwald, H. J C [UNESP]; Torres, M. A S [UNESP]; Pinto Júnior, C. C E [UNESP] (Elsevier, 1991)
In variable-amplitude loading there are interaction effects between the loading history and the crack propagation rate. The most important of these effects is the retardation in the crack propagation, which may raise the life of the cracked structureconsiderably. The main objective of this research is to analyse and quantify the retardation of crack propagation in a thin plate of the high-resistance aluminium alloy 2024-T3, comparing the results obtained from the mathematical models proposed to account for the retardation effect. The specimens were tested under high-low loading sequences, for different crack sizes and overload ratios. A simplified model was developed, based on crack closure theory, that could represent the crack behaviour during retardation very well. © 1991.
Keywords: crack growth; retardation